Identifying the role of Information Systems to implement Information Security System - Siew Poh Phung, Dr.; Valliappan Raju, Assoc. Prof. Dr.; Haji Zanial, Tuan (International Journal of Engineering and Technology, 2019)
Given that data forms a crucial resource in the contemporary world, especially in situations such as those involving handling crime, guidelines or benchmarks have evolved to support the security of the data. This paper presents different forms of data security principles and culminates into an examination of crucial data security measures that are worth embracing. Specific data security guidelines that the paper presents include COBIT, ITIL, PCIDSS, BS 7799, AND ISO27001. The study’s central objective is to highlight a state of standardization and position that the respective standards exhibit, as well as different countries’ appropriations and the ease of use of these guidelines.